DEMOGRAPHIC COMPOSITION OF REGIONAL POPULATION REPAIR: PROBLEMS AND PROSPECTS - Babiak, Halyna; Mesaksudi, Tetiana (Регіональні аспекти розвитку продуктивних сил України, 2018)
The article is about problems of reproduction of the population of Ternopil region. Substantiated demographic policy is an important factor in regulating population reproduction processes. It should have influence on the formation of the society’s desired mode of reproduction of the population or preservation of changes in trends in the dynamics of population and structure of population, the pace of their changes, dynamics of birth rate, mortality, family composition, internal and external migration, qualitative characteristics of the population. It is necessary to develop and approve the Concept of Demographic Development of Society if we want to improve the current demographic situation in Ukraine and in the Ternopil region. An assessment of trends in the demographic development of the Ternopil region is presented in this article. Authors concludedthat the current demographic situation is negative after studying demographic processes in the region. The population is reduced due to natural and mechanical movements. Analyzing the current state of the development of demographic processes in the Ternopil region, it is advisable to identify trends in population changes in the future. Therefore in this article we made evaluation of the prospects of population development in the region. The article contains information about population in Ternopil region and that it will decrease in the future. Therefore, the development of effective demographic policies is necessary. It would stop the negative processes of reproduction of the population, by changing the direction of their development. It involves real and specific steps for the d evelopment of the economy, the social sphere and improve the living level of the region. Practical recommendations on the perspective and ways of improving the demographic situation in the region are developed in the article.